Software Solution of Web Questionnaires for the Analysis of the Economy in Relation to the Competence of Students - Simeunović, Vlado; Milic, Sanja (Asian Journal of Education and Training, 2018)
The basic idea of the research was to take advantage of IT and establish a direct contact between businesses (employers) and universities in order to exchange relevant data on the knowledge, skills and competencies of students who got their first job in the economy. We used the best practices from previous papers that dealt with designing web questionnaires to more or less similar theme. We created the instruments for data collection which represent the essence of the research, conducted the survey, and programmed the software. The questionnaire is based on Likert-type questions. The programming is done in familiar web technologies. Relying on existing theoretical knowledge we modeled the research, and we are in the first part we constructed an instrument (a questionnaire with 44 questions of Likert type), performed necessary determining of its metric values, and then created a web application for its easy use. As a result of the specific method of programming and designing of pages, we got a functional software that presents web questionnaire which employers can access and evaluate newly hired students.